FA’ALIAT BERNAMAJ HIFZU AL-MUFRADAT LIFAHM QIRA’AT FII ALLUGHAT AL-‘ARABIYAT LITULAAB AL-FASL SABI’ BII MA’HAD BAHARUDDIN JANJI MUARA TAIS - Musyrifah Hakim Nasution (An-Nahdah Al-'Arabiyah, 2023)
Memorizing Arabic vocabulary is an activity that is expected to improve understanding of Qira’ah in Arabic in learning. The besic problem of this research is that most of the ability to understand Qira’ah in Arabic for the seventh students at the Baharuddin Islamic Boarding School is still low. The purpose this study was to determine the effectiveness of the mufradat memorization program for understanding Qira’ah in Arabic. As for the methodology used in this study is quantitative, the purpose of quantitative is to establish a hypothesis. The conclusion of this program is that the memorized mufradat program is effective for understanding Qira’ah in Arabic for the seventh students at the Baharuddin Islamic Boarding Janji Maui Muara Tais Angkola sub-district Muara Tais south Tapanuli district. The hypothesis (ha) is accepted and (h0) is rejected.